Accelerator Mass Spectrometry in Laboratory Nuclear Astrophysics. Issue 1 (January 2016) - Nusair, O; Bauder, W.; Gyürky, G; Paul, M; Collon, P; Fülöp, Zs; Greene, J; Kinoshita, N; Palchan, T; Pardo, R; Rehm, K E; Scott, R; et al.
Abstract: The extreme sensitivity and discrimination power of accelerator mass spectrometry (AMS) allows for the search and the detection of rare nuclides either in natural samples or produced in the laboratory. At Argonne National Laboratory, we are developing an AMS setup aimed in particular at the detection of medium and heavy nuclides, relying on the high ion energy achievable with the ATLAS superconducting linear accelerator and on gas-filled magnet isobaric separation. The setup was recently used for the detection of the 146 Sm p -process nuclide and for a new determination of the 146 Sm half-life (68.7 My). AMS plays an important role in the measurement of stellar nuclear reaction cross sections by the activation method, extending thus the technique to the study of production of long-lived radionuclides. Preliminary measurements of the 147 Sm( γ, n ) 146 Sm are described. A measurement of the 142 Nd( α, γ ) 146 Sm and 142 Nd( α, n ) 145 Sm reactions is in preparation. A new laser-ablation method for the feeding of the Electron Cyclotron Resonance (ECR) ion source is described.